THE ROLE OF FUMES EXPOSURE FROM ELECTRIC MOSQUITO REPELLENT CONTAINED ALLETHRIN AGAINST WEIGHT AND COLOUR OF THE RATâS LUNGS - Hayu, Tri Pangesti; Soekanto, Ayly (Universitas Wijaya Kusuma Surabaya, 2016)
Lungs as place where the gases exchange inside the body is related to enviroment sorrounding. Usage of electric mosquito repellent that contained allethrin on certain period can inflict lungâs abnormalities.The aim to this research is to find the effect of fumes exposure from the electric mosquito repellent that contained allethrin to weight and colour of ratâs lungs. The research was experimental laboratory. 24 male rats strain Wistar that devided into 4 groups, which were group 1 control (P0) without exposure, group 2 (P1) exposed 4 hours a day, group 3 (P2) exposed 6 hours a day and group 4 (P3) exposed 8 hours a day. In 30 th day, the rats terminated in the order to taken their lungs organ by operation. The purpose of taken the lungs was analyzed lungâs weight and alteration of its colour. The acquired data process by Anova test for weight analysis, and Kruskal Wallis test for colour change analysis, respectively with significant value (Î± < 0,05). The result of anova test is (Î± = 0.004) and kruskal wallis test is (Î± = 0,001), that to mean there are significan differentiation in group. Conclusion of this research : there was an effects of fumes exposure of electric mosquito repellent that contain allethrin against the weight and colour of the ratâs lungs. That effect on the lungs occour because collaps of the alveolus or lungs.